Massed and spaced training build up different components of long-term habituation in the crab Chasmagnathus - Pedreira, M.E. (1998)
The crab Chasmagnathus granulatus reacts to a shadow passing overhead with an escape response that habituates after 30 trials and for 5 days at least. The effect of a wide range of different intertrial intervals (ITIs) (0, 9, 27, 45, 81, 135, and 171 sec) on the Chasmagnathus long-term habituation (LTH) was evaluated at 24 h. Memory retention was estimated separately at two phases of a six-trial testing session: at first trial (the initial testing phase) and at the subsequent block of five trials (the retraining phase). A training of 30 trials with an ITI equal to or longer than 27 sec induced LTH at both testing phases, however, with a 0- or a 9- sec ITI, training wholly failed to build up LTH. When the number of trials was increased, a massed training (ITI = 0 or 9 sec) induced LTH at re- training but not at initial testing. Thus, massed training produces LTH only at retraining, whereas spaced training (ITI ≤ 27 sec) produces LTH at both initial phase and retraining. An ITI shift from training to testing diminished or abolished retention at retraining regardless of the direction of the shift, thus suggesting that crabs acquire a memory of the trial- spacing at training. According to these results, it is postulated that LTH consists of two memory components: one produced by spaced training and expressed at both initial testing and retraining, and one yielded by massed training and expressed only at retraining. The possibility that the two components of LTH were differentially affected by cycloxemide and context shift is discussed.